Comparative Study for Photodegradation of Remazol Red R by Different TiO2 Samples (Dhaka University Journal of Science, 2017)
Potassium dichromate modified TiO2 photocatalyst (MD-TiO2) was prepared and its photocatalytic activity was compared with that of ordinary commercial TiO2 (C-TiO2) and special Degussa P25 TiO2 (D-TiO2). An organic dye, remozol red R(RRR) was used as a substrate for photodegradation from aqueous solution into environmentally safe products such as water, carbon dioxide and mineral ions. The photodegradation of RRR was carried out by varying the concentration of different types of TiO2 suspension, initial concentrations of dyes between 0.5× 10-4 M and 2.5 ×10-4 M, pH between 2.0 and 6.0 and light sources which are UV, artificial visible and sunlight. With increasing the catalyst concentration, percent degradation was found to increase up to a concentration of 1.2 g/100 mL of C-TiO2, 0.12 g/ 100 mL of D-TiO2 and 0.10 g/100 mL of modified MD-TiO2 for a definite concentration of RRR. However, RRR shows adsorption on TiO2 samples except C-TiO2. Again, the photodegradation efficiency is inversely affected by the dye concentration. Thus, the removal efficiency was found to be influenced by all of the above parameters. The maximum removal efficiency is found at pH 3.0 under sunlight in the presence of modified MD-TiO2,which suggests that MD-TiO2 can be used as an effective material for the removal of RRR instead of C-TiO2 and D-TiO2.Dhaka Univ. J. Sci. 65(1): 49-54, 2017 (January)